CHARACTERISATION AND AREA-SPECIFIC RESISTANCE ANALYSIS OF BARIUM STRONTIUM COBALT FERRITE - SAMARIUM DOPED CERIA CARBONATE - ARGENTUM FOR SOLID OXIDE FUEL CELLS - Umira Asyikin Yusop, Umira Asyikin Yusop; Muhammad Nur Fikri Osman, Muhammad Nur Fikri Osman; Muhammad Zul Idzham Abdul Ghani, Muhammad Zul Idzham Abdul Ghani; Mohd Azham Azmi, Mohd Azham Azmi; Tan Kang Huai, Tan Kang Huai; Nurul Akidah Baharuddin, Nurul Akidah Baharuddin; Hamimah Abd Rahman, Hamimah Abd Rahman (2023)
One of the most challenging aspects of fuel cell technology is searching for appropriate materials that can address and compensate for solid oxide fuel cell (SOFC) weaknesses. This study focuses on a barium strontium cobalt ferrite-samarium doped ceria carbonate-argentum (BSCF-SDCC-Ag). Some experimental work has been done to investigate the material’s potential use in low-temperature SOFCs. The experimental variables include chemical, physical, and electrochemical characteristics. The phase identification of the composite cathode powder was analysed and showed that all element intensity peaks appear at their respective JCPDS numbers, with no secondary peaks occurring. The morphology and element distribution analysis illustrated micrograph images and the mapping of the material demonstrated that all elements are properly distributed and mixed. Based on the findings of the porosity and density tests, each sample contained the acceptable range value of porosity between 21.12 % and 22.50 %. The electrochemical performance was analysed at 400 C, 500 C and 600 C. In comparison to BSCF-SDCC, BSCF-SDCC-Ag 1 wt% had a greater ASR value. The ASR value drops in the BSCF-SDCCAg 3 wt% sample while increasing in the BSCF-SDCC-Ag 5 wt% sample. Apparently, when the temperature is set to high, the ASR value is inconsistent. This might be due to the symmetrical cell sample condition, since its surface is cracked. Overall, the BSCF-SDCC-Ag 3 % contributes to a decrease in the ASR value at temperatures 400 C and 500 C, but at 600 C has a slight increase in ASR value of approximately 10.4 %. Thus, further exploration of the production technique and preparation procedure is crucial to ensure the cathode reliability and performance for SOFC application.